2020
DOI: 10.3389/fchem.2020.00819
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Synthesis and Electro-Optical Properties of Dibenzothiophene/Thiophene Conjugated Polymers With Stepwise Enhanced Conjugation Lengths

Abstract: A total of six conjugated polymers, namely PDBT-Th, PDBT-Th:Th, PDBT-2Th, PDBT-Th:2Th, PDBT-2Th:Th, and PDBT-2Th:2Th, consisting of dibenzothiophene, thiophene, and bithiophene were electrochemically synthesized. Their electrochemical and electrochromic properties were investigated in relation to the conjugation chain lengths of the thiophene units in the conjugated backbones. Density functional theory (DFT) calculations showed that longer conjugation lengths resulted in decreased HOMO-LUMO gaps in the polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…† It is well-known that a successful electrochemical copolymerization occurs when the E onset of different monomers are close to each other. 22,35 In our case, it was found that the difference in the E onset of the EDOT (1.11 V) and the DTT (1.07 V) is as low as 0.04 V, which suggests the feasibility of electro-copolymerization. From this point, the monomers EDOT and DTT are revealed to get oxidized within the same potential range and radical cations of both monomers might form simultaneously on the ITO surface where they can react with each other and form a copolymer.…”
Section: Electrochemical Copolymerizationmentioning
confidence: 53%
See 1 more Smart Citation
“…† It is well-known that a successful electrochemical copolymerization occurs when the E onset of different monomers are close to each other. 22,35 In our case, it was found that the difference in the E onset of the EDOT (1.11 V) and the DTT (1.07 V) is as low as 0.04 V, which suggests the feasibility of electro-copolymerization. From this point, the monomers EDOT and DTT are revealed to get oxidized within the same potential range and radical cations of both monomers might form simultaneously on the ITO surface where they can react with each other and form a copolymer.…”
Section: Electrochemical Copolymerizationmentioning
confidence: 53%
“…33 The advantages of electrochemical deposition are (i) small amounts of precursor are required and high purity polymer lms are obtained (ii) the technique is fast and environmentally friendly (iii) electrochemical reactions are carried out at room temperature, (iv) controllable parameters such as the thickness of lm, deposition time, etc. [34][35][36] Moreover, an effective electrochemical copolymerization occurs when the oxidation potentials of two monomers are close to each other. 37,38 Herein, both monomers EDOT (oxidation potential 1.11 V) and DTT (oxidation potential 1.07 V) could be oxidized simultaneously within the same potential range and react with each other to form copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…11 In 2020, Lin et al designed six conjugated copolymers using thiophene as a fundamental unit, which all exhibited significantly improved electrochemical stability and noteworthy color changes when transitioning from the oxidized to neutral state with increasing conjugation length. 12 In the same year, Zhen Xu and coworkers synthesized a novel copolymer PEM-11 via electrochemical copolymerization of two donoracceptor type monomers, which exhibited stable ndoping, favorable cycle stability, and a lower electrochemical/optical band gap. The results suggested that the obtained copolymer could be a promising candidate for electrochromic windows, e-papers, or eyewear applications.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the prepared films only formed on the electrodes without any obvious signs of a reaction in the solution. Moreover, the electropolymerization approach uses inexpensive supporting electrolytes instead of specialized catalysts and expensive complexants for solution-phase synthesis 12,15,16 . However, the choice of applied voltage in the electropolymerization process can significantly affect the growth rate and quality of the produced polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, CPs based on heteroaromatic monomers have received significant interest due to their special electrical, electrochemical, mechanical and optical properties which are all related to: the effective interactions of HOMO (Highest Occupied Molecular Orbital)-LUMO (Lowest Unoccupied Molecular Orbital), diversity of the heteroatoms, high emission efficiencies, tunability of their band gaps and high thermal stabilities. [13][14][15] Especially in the last two decades, efforts have been directed toward the synthesis of conjugated heteroaromatic polymers (CHAPs) via various techniques including electrochemical, [13,16,17] chemical [18,19] and photochemical polymerization processes. [20][21][22] For the electrochemical synthesis of CHAPs, researchers have primarily relied on cyclic voltammetry, potentiostatic, galvanostatic, and charge discharging methodologies.…”
Section: Introductionmentioning
confidence: 99%